Provitamin " A " in Seaweeds of Lake Rezayeh - F. Plattner (Acta Medica Iranica, 1960)
Colorimetric estimation of Carotene in Enteromorpha intestinalis, a se.awe~d of the family of Ulvaceans abounding in the Lake of Rez?,yeh, has. proved ?' Vlt~rrlln activity of this plant corresponding to 3000 Internatlonal Umts of vitamin A approximately.